Spectral Properties of Pr3+‐Doped Transparent‐Glass‐Ceramic Containing Ca5(PO4)3F Nanocrystals. Issue 11 (26th August 2013) - Huang, Jianhua; Zhang, Sinian; Chen, Yujing; Gong, Xinghong; Lin, Yanfu; Luo, Zundu; Huang, Yidong
Abstract : A Pr 3+ ‐doped transparent oxyfluoride glass‐ceramic containing Ca5 (PO4 )3 F nanocrystals was prepared by melt quenching and subsequent thermal treatment. The crystallization phase and morphology of the Ca5 (PO4 )3 F nanocrystals were investigated by X‐ray diffraction and transmission electron microscope, respectively. The volume fraction of the Ca5 (PO4 )3 F nanocrystals in the glass‐ceramic is about 10% and the fraction of Pr 3+ ions incorporated into the Ca5 (PO4 )3 F nanocrystals is about 22%. The peak absorption cross sections at 435 and 574 nm increase up to 128% and 132% after crystallization, respectively. The peak stimulated emission cross sections of the 3 P 0 → 3 H 4 blue laser channel and 3 P 0 → 3 F 2 red laser channel for the glass‐ceramic are 4.95 × 10 −20 and 29.8 × 10 −20 cm 2, respectively. The spectral properties indicate that the glass‐ceramic is a potential visible laser material.